ANALISIS ABNORMAL RETURN PORTOFOLIO WINNER - LOSER PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100 - Jessica Willa Wiranata; Anastasia Sri Mendari (Program Studi Ekonomi Manajemen Fakultas Ekonomi Universitas Simalungun, 2021)
This study aims to analyze whether there is a difference in abnormal return average of stock portfolios in winner and loser categories during two different periods namely formation and testing periods to test winner-loser anomaly occurrence. The population of this study was the companies listed in the Kompas 100 Index of Indonesia Stock Exchange from February 2015 to July 2019. A number of 44 companiesused as the samples of this study which selected by using the purposive sampling technique. Parametric paired sample t-test and nonparametric Wilcoxon signed ranks test were used to analyze the data that processed by using SPSS program. The results show that the abnormal return average of the winner stock portfolio and loser stock portfolio in the formation period has a significant difference with the abnormal return average of the winner stock portfolio and loser stock portfolio in the testing period.